2014
DOI: 10.1021/sc500635e
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Cadmium by Waste Shell Dust of Fresh Water Mussel Lamellidens marginalis: Implications for Metal Bioremediation

Abstract: The ability of the shell dust of freshwater mussel Lamellidens marginalis (MSD) to remove cadmium from the aquatic system was evaluated. The results indicate that MSD, a waste biomaterial, bears the potential to remove cadmium from contaminated water with a biosorption capacity of 18.18 mg g −1 at pH 6. At equilibrium, the adsorption data fitted to Langmuir (r 2 = 0.992) significantly more than the Freundlich equation (r 2 = 0.66). Regression analysis suggests that the biosorption kinetics followed the pseudo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 41 publications
(59 reference statements)
3
37
0
Order By: Relevance
“…Following collection and identication, the esh of the mussels were removed and the shells were washed under running water and then sun dried. 53,54 Further, the esh remnant, if any, attached to the shells were removed carefully, prior to the use in the experiments. In order to carry out the characterization of the shells, 23 shells of C bensoni and 18 shells of L. marginalis were randomly picked from the collections.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Following collection and identication, the esh of the mussels were removed and the shells were washed under running water and then sun dried. 53,54 Further, the esh remnant, if any, attached to the shells were removed carefully, prior to the use in the experiments. In order to carry out the characterization of the shells, 23 shells of C bensoni and 18 shells of L. marginalis were randomly picked from the collections.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…49 Alternatively, the compost bivalve shells can be used, which are more effective than the freshly derived oyster shells. 50 The shells of the mussels and snails are cost effective biosorbent that can be used for the purpose of metal and dye removal, 36,51,52 directly as akes or granules 53,54 or through the formation of hydroxyapatite. 55 The shells of the bivalves are also considered suitable as llers and for the use as a substitute to mortar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pollution of aquatic ecosystems with heavy metal ions such as cadmium is one of the major outlets of metal ion toxicity affecting humans because a large number of number of aquatic resources are used by man for different activities therefore raising the possibility of potential health risk from the contamination of this resource (Hossain et al, 2015). For example wastewater discharges from industrial activities has been reported as one of the main outlets of aquatic pollution from heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…These beneficial uses of cadmium in industrial processes have led to increased cadmium transport within the proximity of man's environment. However, poor environmental practices has led to their introduction into the food web at magnified levels resulting in cadmium interfering with the physiological, behavioural and biochemical processes in man (Prapagdee et al, 2014;6 Bernard, 2008;Johri et al, 2010;Hossain et al, 2015). The significance of this problem has led to the inclusion of cadmium as one of the priority pollutants that should be eliminated from drinking water and discharged effluents by the United States Environmental Protection Agency (USEPA) and the World Health Organisation (WHO).…”
Section: Introductionmentioning
confidence: 99%